Application of the Fuzzy Method in the Design of Control and Monitoring Systems for Flood Canal Pump Houses - Lukman Medriavin Silalahi; Linggar Amnesta Virgian (CCIT (Creative Communication and Innovative Technology) Journal, 2021)
The purpose of making a prototype of the canal to flood the pump house is namely as a means of ideas that may later be applied to the pump house in Indonesia. At the end of this task will be made protorype flood canal house pump with which it can work according to the speed of the incoming flow and the height of the water in the canal, on hulu there are 1 pump 12V which will drain the water into the canal and also waterflow as a tool that can detect the incoming flow. At the pump house there are 3 pump and 1 water level which will work according to the inflow and the height of the channel. Fuzzy Logic is one method of system control can provide decision that resembles the human decision. In the design process of this plant, used a system of development control of the fuzzy logic system using Arduino. It is intended for a design on the plant control system and monitoring of the pump house flood canal. The use of the Speed Controller PWM on the circuit can work well in regulating the pump speed in the work. Pump 1 and pump 2 has a maximum value of the PWM 144 that can remove water 180 ml that works on low currents and are and sodetan have the value of the PWM to 255 that can get water out of 318 ml of working on a heavy flow.